Agreement with William Holmes, - McLoughlin, John, 1784-1857
One agreement between John McLoughlin of Oregon City, and William Holmes of Oregon City. In this agreement, Holmes agrees to pay McLoughlin $3,000 for the purchase of some property in Oregon City. The details of the property are given. Holmes agrees to build a fire proof brick store and dividing wall. The document is signed.